El aprendizaje de la escritura - Burón Castro, Taurino (Estudios humanísticos. Geografía, historia y arte, 1993)
In this article has been studied many pieces for leaning of writting between XIth and XIXth centuries; some of the determinating factors like tools and parchment in the type of letters, influences between Middle Age Paleography and Renaissance Calligraphy; also plays part in the letter diffusion, colleges and the Notarial Institution, across the several residuals lines about the methode used to write over codex in protocols of the XVIth century. It's been valued the script as a modern ornamental manifestation. Concluding, Libraires and Archives through the respectives printed papers and manuscripts constitute the best school for a beginner of calligraphy and for studing of the strip evolution. The area of documentation it' s limited to the provincial ambit of Leon.